Comparison of computerized and standard cognitive test in Thai memory clinic - Pornpatr A. Dharmasaroja (2019)
© 2018 Journal of Neurosciences in Rural Practice | Published by Wolters Kluwer - Medknow. Background: Computer-based Thai Cognitive Test or Computer-based Thai Mental State Examination (cTMSE) was developed aiming to help doctors to easily get the accurate results of TMSE in a routine, busy outpatient clinics. The purpose of this study was to compare the evaluation process in terms of feasibility, duration of the test, participants/administrator preference, and the results of cognitive test between cTMSE and the standard Thai Mental State Examination (sTMSE). Methods: Twenty-two elderly participants (>60 years old) who were not demented and 22 patients with mild-to-moderate dementia were included in the study. All participants would be asked to have TMSE by standard method (sTMSE) and computer-based method (cTMSE), at least 2 weeks and up to 2 months apart. Scores and duration of the test were compared using dependent paired t-test. Agreement of the tests between two methods and Kappa statistics were analyzed. Results: Paired t-test showed no significant difference in scores between the two methods (mean sTMSE vs. cTMSE: 22.84 vs. 22.62, 95% confidence interval [CI]: [-0.465] to 0.987, P = 0.524). Percent of agreement between the two methods was 92.5%, with the Kappa of 0.85 (P < 0.001). Duration of the test by sTMSE was slightly shorter than the cTMSE (7.31 min vs. 7.97 min, 95% CI: [-1.159] to [-0.175], P = 0.09). Overall, participants liked being tested by cTMSE more than sTMSE. Conclusion: Computer-based TMSE was feasible to use and accurate for screening in aging adults and for cognitive evaluation in patients with mild-to-moderate dementia.